2012
DOI: 10.4103/1817-1737.102184
|View full text |Cite
|
Sign up to set email alerts
|

Patient-related independent clinical risk factors for early complications following Nd: YAG laser resection of lung cancer

Abstract: INTRODUCTION:Neodymium:yttrium aluminum garnet (Nd:YAG) laser resection is one of the most established interventional pulmonology techniques for immediate debulking of malignant central airway obstruction (CAO). The major aim of this study was to investigate the complication rate and identify clinical risk factors for complications in patients with advanced lung cancer.METHODS:In the period from January 2006 to January 2011, data sufficient for analysis were identified in 464 patients. Nd:YAG laser resection d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Alternative uses for the laser have been proposed [10,11], including treatment of endobronchial tumors with curative intent. Unfortunately, these research projects are mostly limited by small samples and retrospective analyses.…”
Section: Only Patients With Central Airway Obstruction Were Includedmentioning
confidence: 99%
“…Alternative uses for the laser have been proposed [10,11], including treatment of endobronchial tumors with curative intent. Unfortunately, these research projects are mostly limited by small samples and retrospective analyses.…”
Section: Only Patients With Central Airway Obstruction Were Includedmentioning
confidence: 99%
“…Although most of these studies were not designed to elucidate risk factors for complications of therapeutic bronchoscopy, one which did evaluated 464 patients undergoing laser treatment of malignant CAO. They found that older age, hypertension, and chronic obstructive pulmonary disease (COPD) were independent risk factors for complications of laser treatment [30]. Another group reviewing a series of 195 stent procedures performed in 172 patients found that the type of stent used was associated with certain complications, including infection for Aero stents and migration for Dumon silicone tube stents [37].…”
Section: Complications Of Therapeutic Bronchoscopy For Malignant Cent...mentioning
confidence: 99%
“…These studies have a great deal of heterogeneity in terms of the type and etiology of CAO, the techniques used to relieve it, and their definitions of complications [28]. With that said most studies of therapeutic bronchoscopy report low overall acute complication rates ranging from 0% to 18% with the majority of these characterized as mild [13,16,21,28–31]. Long-term complications are more common with airway stent procedures than other therapeutic techniques with some series reporting rates between 10% and 60% [32–35,36 ▪ ].…”
Section: Introductionmentioning
confidence: 99%